Credit Risk Management Analysis at PNM Mekar, Bumiratu Nuban District, Lampung Regency - Ainun Farichah; Finny Ligery; Ahmad Mukhlishin (LP2M IAIN Palopo, 2026)
This study aims to analyze the credit risk management strategies implemented by PNM Mekaar in Bumi Ratu Nuban District, Central Lampung Regency, and to examine their relevance to Islamic economic values. The background of this research stems from the high risk of non-performing loans (NPL) in microfinance institutions, which can potentially disrupt institutional stability and the sustainability of community empowerment programs. The study employs a descriptive qualitative approach, with data collected through in-depth interviews with management, field staff, and clients, supported by observation and documentation. The findings indicate that credit risk management strategies at PNM Mekaar are carried out through a group responsibility system, weekly monitoring, business mentoring, and credit restructuring for clients experiencing financial difficulties. These strategies are relatively effective in reducing non-performing loans, although challenges remain, including low financial literacy, limited field facilitators, and external economic factors. From the perspective of Islamic economics, these practices align with the concepts of dhaman jama’i (collective guarantee), hisbah (social oversight), al-amanah (trustworthiness), and the principle of leniency for debtors as prescribed in the Qur’an. The study concludes that credit risk management at PNM Mekaar not only serves to maintain institutional soundness but also reflects the values of justice, solidarity, and the objectives of maqashid sharia in protecting wealth (hifdz al-mal) and enhancing community welfare. These findings are expected to provide practical contributions for PNM Mekaar in strengthening risk mitigation strategies and academic contributions to the literature on credit risk management in microfinance institutions from an Islamic perspective